The Role of Expressive Values of Smart Materials in Influencing the Quality of Interior Design Functionally and Aesthetically - Obeidat , Saif (Dirasat: Human and Social Sciences, 2022)
There is an important role the expressive values of smart materials play in influencing the quality and efficiency of interior design and its reflection on the behavior of individuals. Materials are generally one of the most important complementary elements that the interior designer resorts to during the design process in its various forms. The research problem is that some interior designers are not aware of the importance of using and employing smart materials, which leads to a problem and reduces the efficiency and effectiveness of these environments. The research aims to assess the role of expressive values resultingfrom the use of smart materials in the process of interior design in built environments by exploiting these materials in the design of ceilings, floors, walls, furniture, and lighting in the built environment. The significance is summarized by providing some explanations, examples, and limitations that can be followed by interior designers in order to enhance the quality of the interior design process in built environments, by using and employing smart materials in the design process, and providing some realistic applications of the expressive values of materials. The methodology that was used is descriptive analysis. The researcher distributed a questionnaire to a random sample of individuals present within their built environments. The results came to clarify the role that the expressive values of smart materials play in raising the quality of interior design, depending on the characteristics that these materials have, which contribute to raising the effectiveness of the built environment.